Criteria for Educational Projecting in Social and Health Services - Maria Grazia Simone (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
The goal of the article is to reflect on the meaning of the action of projecting in socio-educational services and in environments that take care of the health of citizens, children, vulnerable people. The result that the article reaches is to offer a series of useful criteria for those who have to design within this kind of services that take care of the often vulnerable person.